Characteristics of balance performance in the Chinese elderly by age and gender - Hongmei Wu; Yifan Wei; Xiangqi Miao; Xia Li; Yang Feng; Zhenzhen Yuan; Peng Zhou; Xiaolei Ye; Jianhong Zhu; Yu Jiang; Qinghua Xia (BMC Geriatrics, 2021)
Abstract Background Population aging has been an emerging public and health concern globally. Balance performance can be applied as an indicator of functional status and a predictor of health outcomes in the elderly. However, reference data of balance performance in the elderly generated from large scale studies have been very limited. In research and geriatric assessment settings, the age and gender specific data on balance performance are indispensable prerequisites for identifying subpopulation with and at risk of impairments and subsequently implementing targeted interventions in clinics and public health to improve their balance performance. Methods A total of 1984 elderly subjects aged 60 to 97 years from community settings in urban China were investigated. The balance performances together with 3 individual domains and 16 items were evaluated using the X16 balance testing scale. Results In the elderly, with age increases each item, individual domain, and overall balance performance scores decreased gradually. Meanwhile, individual variations of individual domains and overall balance performance were all increased over age. Relative to levels of 60- years, postural stability and overall balance performance decreased significantly since 65 years old, static balance and dynamic balance capacities started to decrease significantly since 70 years old. There was no significant difference in each balance domain and overall balance performance between men and women. Across age groups, portions of individuals able to perform task 4, 8 and 11 successfully were the lowest amongst their corresponding domains static balance, postural stability, and dynamic balance, respectively. Similar patterns were observed in both men and women. Balance performances were categorized into poor, fair, and good groups with scores of 0 to 10, 11 to 17, and 18 to 20, respectively. With increases of age, proportions with poor and fair balance capacities elevated stably. Conclusions In the elderly, with advances in age, abilities of overall balance performance, individual domains of static balance, postural stability, and dynamic balance, and successful performances on specific tasks declined gradually and stably. The deterioration started to be obvious since 65–75 years. Men and women had similar patterns.